(untitled) (Journal of Shaheed Suhrawardy Medical College, 2018)
Krukenberg tumour is metastatic ovarian involvement of adenocarcinoma in women of reproductive age group. The primary site is commonly in stomach but less commonly from other parts of gastrointestinal tract and uncommonly from other organs. The route of metastasis of this tumour is still not proven though the raw ovarian surface and transperitoneal invitation of malignant cell is one of the postulations. As is the etiology so is the resection of either ovarian or gastric tumour failed to show any improvement of this condition. Ovarian resection can be done in the form of salphingo-oophorectomy with or without hysterectomy. Gastric resection is also done in the same or subsequent sitting according to stage and presentation. We report such an uncommon entity in a 33 year old lady presenting with lower abdominal lump. J Shaheed Suhrawardy Med Coll, June 2017, Vol.9(1); 38-40